2020
DOI: 10.1002/asi.24436
|View full text |Cite
|
Sign up to set email alerts
|

Predicting users' continued engagement in online health communities from the quantity and quality of received support

Abstract: Online health communities (OHCs) have been major resources for people with similar health concerns to interact with each other. They offer easily accessible platforms for users to seek, receive, and provide supports by posting. Taking the advantage of text mining and machine learning techniques, we identified social support type(s) in each post and a new user's support needs in an OHC. We examined a user's first‐time support‐seeking experience by measuring both quantity and quality of received support. Our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 63 publications
(71 reference statements)
0
35
0
Order By: Relevance
“…Without online education platforms, online education mode couldn't be implemented [27]. The availability of the use rights of online education products, and the usefulness of online education products are two things most concerned by online education platform users [28]. The advantages of online education have well satisfied the users' concerns about the access to use rights [29].…”
Section: A Theoretical Study Of the Acceptance Behavior Of Online Educationmentioning
confidence: 99%
“…Without online education platforms, online education mode couldn't be implemented [27]. The availability of the use rights of online education products, and the usefulness of online education products are two things most concerned by online education platform users [28]. The advantages of online education have well satisfied the users' concerns about the access to use rights [29].…”
Section: A Theoretical Study Of the Acceptance Behavior Of Online Educationmentioning
confidence: 99%
“…The second research stream focuses on designing interventions to improve user engagement. System design [3,10], social support [11,12], gamification [13,14], and channels [15] are the most frequently investigated interventions to promote user engagement. For the system design, Baumel and Kane [10] found that therapeutic persuasiveness, therapeutic alliance, visual design, and content predict an increase in user engagement with eHealth interventions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, the more engaged members were, the more positive their health expectations were. Wang et al [12] revealed that the amount and match of received support were positive and significant predictors of new users' continued engagement. For gamification, Edney et al [13] found that the inclusion of gamified features enhanced engagement in an app-based physical activity intervention.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations